2023
DOI: 10.1039/d2ce01612e
|View full text |Cite
|
Sign up to set email alerts
|

A quaternary solid-form of ritonavir: an oxalate salt oxalic acid co-crystal acetone solvate

Abstract: Ritonavir has been reported in seven crystal forms notably form I, II, IIIb and IV, as well as a hydrate, an L-tyrosine co-crystal and a formamide solvate. A new form...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 7 publications
(14 citation statements)
references
References 36 publications
1
2
0
Order By: Relevance
“…There is a reduction in the percentage contribution with an increasing radial intermolecular distance highlighting the short-range of the intermolecular interactions and significance of nearest neighbor synthons in terms of the crystal lattice stabilization. The data reveal that the two polymorphs have quite similar energetic pathways in terms of their molecular assembly at nucleation which is consistent with their concomitant polymorphic behavior, in contrast to other molecular compounds such as p -aminobenzoic acid, , l -glutamic acid, and ritonavir. , …”
Section: Results and Discussionsupporting
confidence: 66%
See 1 more Smart Citation
“…There is a reduction in the percentage contribution with an increasing radial intermolecular distance highlighting the short-range of the intermolecular interactions and significance of nearest neighbor synthons in terms of the crystal lattice stabilization. The data reveal that the two polymorphs have quite similar energetic pathways in terms of their molecular assembly at nucleation which is consistent with their concomitant polymorphic behavior, in contrast to other molecular compounds such as p -aminobenzoic acid, , l -glutamic acid, and ritonavir. , …”
Section: Results and Discussionsupporting
confidence: 66%
“…The data reveal that the two polymorphs have quite similar energetic pathways in terms of their molecular assembly at nucleation which is consistent with their concomitant polymorphic behavior, 2 in contrast to other molecular compounds such as p-aminobenzoic acid, 53,54 L-glutamic acid, 55 and ritonavir. 56,57 Examination of the molecular polarizability reveals no significant differences between the molecules in the two polymorphic forms except for the oxygen (O2) in the phenol group (away from the nitro group) and O4, O5 in the nitro group, and carbons (C3, C5) in the aromatic ring group (see a full list of the calculated atomic charges in the Supporting Information, Section S4 (Table S4)).…”
Section: Lattice Energies Theirmentioning
confidence: 99%
“…84−86 Ritonavir is a conformationally flexible molecule, and as such later and more extensive polymorphic screening studies revealed its ability to crystallize in many more different forms with a current landscape encompassing three polymorphs and two solvates, a quaternary solvated cocrystal salt and an amorphous glassy form. [28][29][30][31]33,85,87 Despite these studies, there remains very little available literature data regarding the nucleation behavior of the ritonavir API as a function of supersaturation for a range of organic solvents reflecting, in part, its inherently low crystallizability and high glass forming ability. 88,89 The structures of form I and II polymorphs were determined and thoroughly characterized by Bauer et al 26 Wang et al 28 have subsequently characterized and compared, in significant detail, the crystal chemistry for both forms I and II in terms of their molecular conformations, polarizabilities, hydrogen bonding networks, intermolecular packing structures, and crystal morphologies and have cross-correlated these to a wider assessment of their crystallizability behavior and respective surface properties.…”
Section: Molecular and Crystal Chemistry And Their Interrelationshipmentioning
confidence: 99%
“…The detailed analysis of the HB networks for both forms I and II can be found in the literature (e.g., refs 28,29) and, as discussed, 26 a significant distinguishing difference of the HB structure between the two forms is related to the hydroxyl functional group. For form I, two characteristic intermolecular synthons were identified 28,29 with synthon A I comprising three strong homo intermolecular HBs (Figure 2a).…”
Section: Molecular and Crystal Chemistry And Their Interrelationshipmentioning
confidence: 99%
“…Also included in the structure, hydrogen bonded to each side of the oxalate, are neutral molecules of oxalic acid, which produce linear supramolecular chains. Other examples include the hydrogen oxalate salt of ritonavir that cocrystallizes with oxalic acid, 14 and the tiotropium fumarate salt that cocrystallizes with fumaric acid, 15 both of which feature linear hydrogen oxalate/oxalic acid and/or fumarate/fumaric acid supramolecular chains. To the authors' knowledge, there are no examples of solid forms featuring mixed charges on API molecules.…”
Section: Introductionmentioning
confidence: 99%